2014
DOI: 10.1074/jbc.m114.571935
|View full text |Cite
|
Sign up to set email alerts
|

Solution NMR Structure and Functional Analysis of the Integral Membrane Protein YgaP from Escherichia coli

Abstract: Background: E. coli YgaP is a membrane-bound sulfurtransferase with a cytoplasmic rhodanese domain. Results: The three-dimensional structure is composed of a cytoplasmic rhodanese domain and two transmembrane helices forming the interface of the homodimer. Conclusion:The structure-activity relationship of YgaP suggests a sulfurtransferase activity. Significance: YgaP may have a role in the detoxification of CN Ϫ to the less toxic SCN Ϫ .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 46 publications
5
32
0
Order By: Relevance
“…The average B-factors of the backbone atoms of the first two turns of helix α4 (i.e., residues 67-72) in the structure of the protein prepared with DTT, the structure of the protein prepared without DTT, and the structure from the crystal treated with thiosulfate are progressively increasing with values of 22.69, 25.11, and 32.80, respectively, whereas the average B-factor of the last two turns of this helix (i.e., residues 74-79) remain similar with values of 13.93, 16.00, and 14.77, respectively. The induction of an S-sulfhydration-dependent dynamical destabilization of the α4 helix is also supported by previous NMR titration studies [10]. The T69 cross-peak in [15N,1H]-TROSY spectra undergoes a significant broadening during the titration of the rhodanese domain with 1-4 mM sodium thiosulfate.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The average B-factors of the backbone atoms of the first two turns of helix α4 (i.e., residues 67-72) in the structure of the protein prepared with DTT, the structure of the protein prepared without DTT, and the structure from the crystal treated with thiosulfate are progressively increasing with values of 22.69, 25.11, and 32.80, respectively, whereas the average B-factor of the last two turns of this helix (i.e., residues 74-79) remain similar with values of 13.93, 16.00, and 14.77, respectively. The induction of an S-sulfhydration-dependent dynamical destabilization of the α4 helix is also supported by previous NMR titration studies [10]. The T69 cross-peak in [15N,1H]-TROSY spectra undergoes a significant broadening during the titration of the rhodanese domain with 1-4 mM sodium thiosulfate.…”
Section: Resultssupporting
confidence: 78%
“…The fold of the rhodanese domain of YgaP treated with thiosulfate is essentially the same as that of unmodified protein ( Figure 1A) [10]. Our previous structural studies of this domain showed that the catalytic cysteine C63 of the protein prepared with 1,4-dithiothreitol (DTT) is partially S-nitrosylated, while the same cysteine in the structure of the protein prepared without DTT is both S-nitrosylated and S-sulfhydrated.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Therefore, it is interesting that a rhodanese domain can be found in the membrane proteome of E. coli. It is located at the cytoplasmic side of the membrane protein YgaP [24] (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%
“…1a). Although the physiological role of YgaP is unknown, the catalytic loop of its rhodanese domain, which includes Cys63, is essential for the sulfur transfer activity [21,22,24]. It has been shown that S-nitrosylation inactivates the function of rhodanese domains by nitrosylation of the catalytically active Cys [20,23].…”
Section: Introductionmentioning
confidence: 99%